Avaliação da sustentabilidade da agricultura familiar no Oeste do Estado do Paraná, em propriedades produtoras de mandioca, considerando sua participação nas fecularias - Riedner, Lilian Navrotzki (2014)
This study aimed to verify whether the farms in the western state of Paraná - this research, characterized as producers of cassava - can develop their daily activities on the properties sustainably. Family farming is sustainable when it is ecologically well-founded, economically viable, socially equitable and culturally appropriate. The objective was to evaluate the sustainability of family farming in the western state of Paraná, in cassava producing properties, considering their participation in potato starch. Thus, besides conducting research with farmers, the study also has the support of starch industries located in western Paraná, associated with ATIMOP who agreed to participate in the study and helped understand the dynamics governing the production and marketing of cassava. A sustainability analysis was performed based on the structuring of a questionnaire / interview, based on Bicalho (1998) and adapted by the author, that the end of the analysis identified that the managements and activities in the properties object of the study are sustainable. Was also structured interview that was applied to Professional industries who work with producers of cassava. As a result, it was identified that there are still difficulties in the producer / industry, especially regarding the use of contracts for the sale of the product. It was also identified that the industry is facing a shortage of manpower to harvest the onerous costs of production, sometimes invalidating it. Regarding sustainability, it was possible to find positive actions that indicate sustainability in properties, both in the economic dimension, but also in the social environment. Finally, the study allows us to understand the dynamics of relationships present in which it was possible to understand the difficulties of both parties, and especially the needs and concerns of producers, diagnosing that there are situations where it is possible and there is a sustainable agricultural system being practiced